LAPISAN F3 DI IONOSFER LINTANG RENDAH - Sri Suhartini (Lembaga Penerbangan dan Antariksa Nasional, 2005)
Calculation using the Sheffield University plasmasphere ionosphere model (SUMIP) have shown that under certain conditions an additional layer (F3 layer) can form in the equatorial ionosphere. The F3 layer forms during the morning-noon period in the equatorial region where the combined effect of the upward ExB drift and neutral wind provides vertically upward plasma drift velocity at altitude near and above the F2 peak. The observation results over Biak and Parepare are shown that F3 layer may form in low latitude ionosphere. The observations result over Biak (1.20˚S, 136.04˚E, magnetic latitude 12.18˚S) on January 2005 shown the occurence of the F3 layer 75% of the days from 09:00 to 18:00 local time. The critical frequency of the F3 layer (foF3) exceeds foF2 by about 1 to 3 MHz, and the virtual height h'F3 ranges from 400 to 600 km. Generally, observation result indicate that the formation of F3 layer at low latitude is different with the equatorial region. Where, in addition to the fountain effects, the dynamical processes of the formation of this layer is influenced by the station location relative to the geographic equator.